Preparing Greenhouse Gas Inventory and Determining Emission Reduction Projects in an Organized Industrial Zone - Merve Çakmak Arı; Sibel Başakçılardan Kabakcı (Doğal Afetler ve Çevre Dergisi)
In this study, greenhouse gas emissions caused by natural gas, electricity and diesel fuel consumed within the boundaries of Kütahya 30 August Organized Industrial Zone were calculated and studies were explored for reduction activities. Within the scope of ISO 14064-1 Guidelines and Features Standard for Calculation and Reporting of Greenhouse Gas Emissions and Removal at the Establishment Level” and “ISO 14067 Product Carbon Footprint Calculation Standard”, the amount of greenhouse gases released into the atmosphere was calculated by using the data recorded by the enterprises on a yearly basis. While the direct emissions from natural gas was calculated as 105394.84 tCO2e in 2019, these emissions decreased in 2020 and reached 2019 level again in 2021. Indirect emissions from imported electricity were 64269.12 tCO2e in 2019, while electricity-related emissions increased in 2020 and 2021. Direct emissions from diesel are considerably lower than those from natural gas and electricity in terms of quantity. However, while the emissions from diesel fuel was 74.11 tCO2e in 2019, these emissions decreased by 75.5% in 2020 and reached 29.49 tCO2e in 2021. A large part of the greenhouse gas generated due to both electricity and natural gas consumption originates from an organization operating in the field of tile-ceramic manufacturing and an organization operating in the field of paper-corrugated cardboard manufacturing. There are many organizations in different fields of activity in organized industrial zones. The study has shown that greenhouse gas emissions must be monitored in these regions and it is necessary to determine the source of greenhouse gas emissions, otherwise the proposed reduction methods will not be very effective.